The COVID-19 Baby Bump: The Unexpected Increase in U.S. Fertility Rates in Response to the Pandemic - Martha J. Bailey; Janet Currie; Hannes Schwandt (Institute of Labor Economics (IZA), 2022)
We use restricted natality microdata covering the universe of U.S. births for 2015-2021 and California births from 2015 to August 2022 to examine the childbearing response to the COVID-19 pandemic. Although fertility rates declined in 2020, these declines appear to reflect reductions in travel to the U.S. Childbearing in the U.S. among foreign-born mothers declined immediately after lockdowns began—nine months too soon to reflect the pandemic's effects on conceptions. We also find that the COVID pandemic resulted in a small "baby bump" among U.S.-born mothers. The 2021 baby bump is the first major reversal in declining U.S. fertility rates since 2007 and was most pronounced for first births and women under age 25, which suggests the pandemic led some women to start their families earlier. Above age 25, the baby bump was also pronounced for women ages 30-34 and women with a college education, who were more likely to benefit from working from home. The data for California track the U.S. data closely and suggest that U.S. births remained elevated through the third quarter of 2022.
Keywords: J13; I14; 330; fertility rates; pregnancy; COVID-19; pandemic; recession